Невозвратный билет: [рассказы] / Маша Трауб - Трауб Маша (Эксмо, 2022)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 58812 / Цена: 377.14 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Т 65 / ГРНТИ: 17.82.32 / ББК: 84(2=411.2)6-44